Avaliação do potencial relativo de mercado, para bens de conveniência, na região sul do Brasil - Sellins, Geraldo (1978)
In abridging the central ideas examined in the present dissertation, we could mention the necessity and importance to the businesman in the possibility to use market potencial datas in the management of his company. The advantages wich derive from the correct use of information about this substance an numberless because for example, they permit abetterdecision about the market zones for the salesman, or then, to distribute according do the buyng capacity of each sales zone, the promotional effort to be used;it also allows to determinate the companies market penetration, and further, permit the establishment of the sales quotas more in line with the salesmen. Another important item of market potencial is that it facilitates the accurate analysis of companies sales. We also approach the theoretical ideas that guide the practi cal development of this dissertation of wich major objective is to inform the "entrepeneur" that sellgoods of convinience of the different potential relative markets, microzone by microzone of the southern states of Brazil, aport of the proceeding a composition of the three hypothesis here described. Abreviating we can acertain two of the hypothesis were already confirmed and that the other wasn't. But there are strong Signs that the process of this comprovation has already begun.